Truth Vibrations - in search of Integrity in the Literary Works and Minds = Wibracje Prawdy - w poszukiwaniu systemu wartości w dziełach literackich i etyki u ich autorów - Trembowski, Alicja (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
What accounts for the value and ethics of a literary work? That words carry energy leads to exerting a powerful impact on those exposed to them. The vibrations of words reflect the soul, which is conditioned by the state of consciousness. Energy, as harmony - is aligned with Truth, Power and the way of Heart, but if in dissonance - it is associated with lack of integrity, disruption and Force.
Keywords: consciousness; kinesiology; literature; integrity; świadomość; kinezjologia; literatura; etyka